2001
DOI: 10.1039/b107881j
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal binding in a carbene complex formed from an imidazolium salt and a metal hydride complex

Abstract: 2-Pyridylmethylimidazolium salts and IrH5(PPh3)2 give an [(N-C)IrH2(PPh3)2]+ species with the imidazole ring bound in the 'wrong way': at C-5, not at the expected C-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
219
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 350 publications
(239 citation statements)
references
References 12 publications
9
219
0
11
Order By: Relevance
“…Only recently, coordination via C4 has been identified as another bonding mode of such carbenes. 7 This bonding mode provides access to a new type of NHC ligands in which the heteroatoms are not located in a,a 0 position but in a,b 0 position with respect to the metal-bound carbon. As a consequence, no canonical resonance form of the carbene can be drawn without introducing additional charges.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, coordination via C4 has been identified as another bonding mode of such carbenes. 7 This bonding mode provides access to a new type of NHC ligands in which the heteroatoms are not located in a,a 0 position but in a,b 0 position with respect to the metal-bound carbon. As a consequence, no canonical resonance form of the carbene can be drawn without introducing additional charges.…”
Section: Introductionmentioning
confidence: 99%
“…3a) were observed, it cannot be discarded that classical and abnormal N-heterocyclic carbenes (NHCs) are formed in situ and these species might act as ligand. 54,55 Therefore, Pd(II)carbene complexes may be formed, most likely by reaction of the imidazolium cation with Pd(0) species. 25,[56][57][58][59] Fig .…”
Section: Synthesis Of Mono-dispersed Pd(0)-nps In Ils and Characterismentioning
confidence: 99%
“…Moreover, they can bind to the metal in a normal (I, III) or abnormal (II) fashion (Scheme 1) with the possibility of both normal and abnormal carbenes arising in a remote position. We have extended Crabtree's terminology 6,7 by using the term abnormal whenever it is not possible to illustrate the carbene structure without charge separation (in contrast to Ia and IIIa). 18 Remote denotes a carbene that contains no stabilizing heteroatom directly adjacent to the carbene carbon.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Only recently it has been shown that an abnormal binding mode via the C4 (or C5) position of imidazolylidenes yields extraordinary electron rich metal centers. [6][7][8][9][10][11][12][13][14][15][16][17] These discoveries led to a considerably increased interest in "non-classical" NHCs, i.e. carbenes that are not stabilized by two adjacent heteroatoms.…”
Section: Introductionmentioning
confidence: 99%